Characterization of tropical Kenny Hill weathered sandstone using non-disruptive testing of pundit and resistivity testing / Noorfaizah Hamzah and Nur'Ain Mat Yusof - Hamzah, Noorfaizah; Mat Yusof, Nur'Ain (Universiti Teknologi MARA, 2022)
Rock characterization of tropical Kenny Hill weathered sandstone have been an effort to be explored by using non-disruptive testing of pundit and resistivity testing to undertake sustainability issues and providing technical approach in exploration of weak rock materials solving. The purpose of this research is to determine the relationship between resistivity and uniaxial compressive strength of the most problematic rock type in Malaysia, namely Kenny Hill weathered sedimentary rocks, more usually referred to as sandstone. According to earlier study, sandstone has degraded in quality and has a tendency to disintegrate due to the tropical climate. Sandstone has a higher strength feature as compared to shale from Bandar Nusa Rhu, Shah Alam. Series of uniaxial compression were carried out to obtain the strength for rock samples. The strength properties of weathered sandstone are studied to quantify the weathering impact to these materials. Resistivity test and Pundit test were laboratory method conducted on the rock samples for verification of the correlation between resistivity and uniaxial compression. Results from the test were analyzed and their relationship with weathering grade was established. It signifies that sandstone strength increasing with the weathering grade.